The PENGEMBANGAN MEDIA PRAKTIKUM BSD (Basic Solution Dilution) BERBASIS ANDROID MENGGUNAKAN TEKNOLOGI AI (Artificial Intelligence) PADA MATERI PENGENCERAN LARUTAN : PENGEMBANGAN MEDIA PRAKTIKUM BSD (Basic Solution Dilution) BERBASIS ANDROID MENGGUNAKAN TEKNOLOGI AI (Artificial Intelligence) PADA MATERI PENGENCERAN LARUTAN - Uliyandari, Mellyta Mellyta; Primairyani, Ariefa (ALOTROP, 2023)
The purpose of this research is to develop an Android-Based BSD (Basic Solution Dilution) practicum media using AI (Artificial Intelligence) Technology in solution dilution material. The development in this study was carried out with a 4D (four-D) define, design, develop, and disseminate. At the definition stage, the formulation of the practicum objectives is carried out, the design stage is carried out by designing the practicum media, while at the development stage the practicum media content validation is carried out by media experts and material experts, the dissemination stage is carried out via youtube. The results showed that the BSD practicum media was feasible to use, this was based on the validation results from two validators, namely material experts and media experts. The practicum media validation score by material experts is at number 69 which is in the "Eligible" category, while the validation results by media experts get 53 which is in the "Eligible" category. The results of the feasibility assessment of practicum media by students also showed results that were in the "appropriate" category with a conversion value of 3.94. Student learning outcomes after using the BSD practicum media also increased when viewed based on the comparison between students' pretest and psotest scores. The average pretest score of students before using BSD media was 50.76 while the average post-test score of students after using BSD media was 80.96. The results of the student's pretest and posttest gain test have a score of 0.61 with the "Medium" category.